2010
DOI: 10.1111/j.1365-294x.2010.04577.x
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic data suggest a role for mosquito-mediated dispersal of West Nile virus across the western United States

Abstract: After introduction, West Nile virus (WNV) spread rapidly across the western United States between the years 2001 and 2004. This westward movement is thought to have been mediated by random dispersive movements of resident birds. Little attention has been placed on the role of mosquito vectors in virus dispersal across North America. The mosquito vector largely responsible for WNV amplification and transmission of WNV in the western USA is Culex tarsalis. Here we present population genetic data that suggest a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 41 publications
0
44
0
Order By: Relevance
“…tarsalis populations in North America. 24,25 This finding could explain why similar CLBOV genotypes have been identified in Manitoba and Colorado. Detailed genetic studies of CLBOVs from geographically isolated Cx.…”
Section: Discussionmentioning
confidence: 79%
“…tarsalis populations in North America. 24,25 This finding could explain why similar CLBOV genotypes have been identified in Manitoba and Colorado. Detailed genetic studies of CLBOVs from geographically isolated Cx.…”
Section: Discussionmentioning
confidence: 79%
“…Nevertheless, more studies are needed to identify vectors and reveal their contribution to host-parasite associations. Indeed, vector movement has been linked to pathogen spread in other systems (42), and such movement, along with changes in vectorhost associations (43), might facilitate parasite host-switching and dispersal. Interestingly, regional studies of ectoparasites of small mammals have shown that flea assemblages can differ more with increasing distance between sampling locations and with increasing differences between local habitat and climate characteristics, even on the same host species (44,45), perhaps because fleas are more exposed to the environment than haemosporidian parasites.…”
Section: Discussionmentioning
confidence: 99%
“…The watershed is in close proximity to the equator, indicating a warmer climate, and well within the currently-documented latitude range of the Aedes aegypti mosquito [8]. The elevation of the watershed's mountain boundaries should naturally isolate the Aedes aegypti vector from external areas, providing a study area with limited external influence [41,42]. Due to its location on the western side of South America, it is also influenced by El Niño/La Niña seasonal variations.…”
Section: Study Sitementioning
confidence: 99%